2020
DOI: 10.1016/j.ijrobp.2019.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 5-Year Progression and Survival Outcomes for Early Stage Non-small Cell Lung Cancer Treated with Stereotactic Ablative Radiation Therapy: Development and Validation of Robust Prognostic Nomograms

Abstract: Purpose: Our purpose was to develop predictive nomograms for overall survival (OS), progression-free survival (PFS), and time-to-progression (TTP) at 5 years in patients with early-stage non-small cell lung cancer (ES-NSCLC) treated with stereotactic ablative radiation therapy (SABR). Methods and Materials: The study cohort included 714 ES-NSCLC patients treated with SABR from 2004-2015 with median follow-up of 59 months, divided into training and testing sets (8:2), with the former used for nomogram developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…CCI, a comprehensive index of multi-morbidities, is a good indicator of a patient’s global status and has been demonstrated to affect the prognosis of patients with lung cancer [ 17 , 23 ]. The variables in the CCI model are readily available and scores can easily be calculated by physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCI, a comprehensive index of multi-morbidities, is a good indicator of a patient’s global status and has been demonstrated to affect the prognosis of patients with lung cancer [ 17 , 23 ]. The variables in the CCI model are readily available and scores can easily be calculated by physicians.…”
Section: Discussionmentioning
confidence: 99%
“…The variables in the CCI model are readily available and scores can easily be calculated by physicians. Recent studies have reached controversial conclusions on the prognostic significance of the CCI [ 17 , 23 , 24 ]. Additionally, no studies have investigated the predictive significance of CCI in patients with NSCLC receiving treatment with PD1 inhibitors; accordingly, so we used a cutoff point of 1 for further investigation, as used by Pylvalainen et al [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The c-index varies between 0 and 1, where a c-index of 1 means a perfect prediction, and a c-index of 0.5 can be interpreted as a random assignment. In biomedical applications and in particular lung cancer survival analysis, a c-index close to 0.7 is considered as satisfying and acceptable 59 , 60 , however, interpretation of the computed c-index value depends on the dataset and the problem at hand.…”
Section: Methodsmentioning
confidence: 99%
“…2 There are serious efforts to improve and develop RT efficacy. 3 It is reported that the inhibition of certain signaling pathways is associated with the enhancement of RT response in several cancer types. 4,5 Proteomics is a large-scale method for determining the changed expression proteins after intervention in the samples.…”
Section: Introductionmentioning
confidence: 99%